2021
DOI: 10.1002/adom.202101523
|View full text |Cite
|
Sign up to set email alerts
|

Superior Performance and Stability of 2D Dion–Jacobson Halide Perovskite Photodetectors Operated under Harsh Conditions without Encapsulation

Abstract: The practical utilization of electronic and optoelectronic materials such as perovskites not only relies on their good device performance and moisture stability but also requires stability under other operating conditions. Herein, the operational stability of the Dion–Jacobson perovskite (DJP) photodetector under different harsh conditions is carefully studied and compared with that of its widely studied counterpart, i.e., the Ruddlesden–Popper perovskite (RPP) photodetector. The DJP‐based photodetector can ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Accordingly, the DJ-type perovskites show superior stability to the RP type. [11][12][13][14] Ahmad et al reported that the DJ-type halide perovskites with 1,3-propanediamine as the spacer cations were much more stable than the RP-type. [15] Zhao et al introduced three new conjugated diamine spacer cations to the DJ-type 2D perovskites, which showed enhanced stability.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the DJ-type perovskites show superior stability to the RP type. [11][12][13][14] Ahmad et al reported that the DJ-type halide perovskites with 1,3-propanediamine as the spacer cations were much more stable than the RP-type. [15] Zhao et al introduced three new conjugated diamine spacer cations to the DJ-type 2D perovskites, which showed enhanced stability.…”
Section: Introductionmentioning
confidence: 99%
“…The highest photodetection parameters obtained in this work are much greater than those of reported HLDP photodetectors (Table S9 †) [14][15][16] and layered DJ perovskites (Table S10 †) [24][25][26][27][28][29][30] and comparable with those of devices based on double perovskites (Cs 2 AgBiBr 6 ; Table S11 †). [31][32][33][34][35] The best performance of (4N4) 2 AgBiBr 8 photodetectors can be explained by their low trap state density (n) and high carrier mobility (m h ) in comparison to the (6N6)SbBr 5 devices.…”
Section: Physicochemical Characterizationmentioning
confidence: 61%
“…Among multifarious marine electrodes, the electrochemical Ag/AgCl electrode 7 has attracted much attention because of its high stability and fast response. 8 However, it is difficult to popularize and use it on a large scale due to the disadvantages of harsh storage conditions 9 and expensive raw materials 10 in practical application. However, the capacitive carbon fiber electrode 11 is a promising marine electrode surmounting the deficiency of traditional electrochemical Ag/AgCl electrodes.…”
Section: Introductionmentioning
confidence: 99%